Strategy to Increase Sales of Coconut Shell Charcoal Briquettes UKM Emas Hitam - Siti Mundari; Herlina (International Conference of Innovation and Community Engagement, 2024)
The use of coconut shell waste is generally used for fuel, household purposes and if sold the price is very cheap. UKM Emas Hitam makes a high-value product, namely making coconut shell charcoal briquettes. The advantage of coconut shell charcoal briquettes with other alternative fuels is that they can produce greater heat. Apart from that, charcoal briquettes from coconut shells are also safer, environmentally friendly, because they do not damage plants and do not cause smoke. The problem that occurs with the UKM Emas Hitam is that its products are purchased by middlemen from Tuban and Bojonegoro in limited quantities and sold wholesale packaged in sacks without any branding. With this method of selling, products cannot compete in the market and are sold at low prices. The solution offered to overcome this sales problem so that it can be increased is that information media, promotion and product sales are needed in the form of a website. With the website, it is hoped that it can reach a wider market and make it easier for consumers to find complete information about the products being sold. Coupled with strong branding and an attractive appearance on the website, it will further increase customer trust, making it easier to get new customers. Meanwhile, the solution to the problem of products being sold wholesale, packaged in sacks without any branding, requires good packaging to be branded as a product brand so that the product can compete in the market and be sold at a higher price.